Dynamic Changes of the Bone Marrow Niche: Mesenchymal Stromal Cells and Their Progeny During Aging and Leukemia - Woods, Kevin; Guezguez, Borhane (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal cells (MSC) are a heterogenous cell population found in a wide range of tissues in the body known for their nutrient-producing and immunomodulatory functions. In the bone marrow (BM), these MSCs are critical for the regulation of hematopoietic stem cells (HSC) that are responsible for daily blood production and functional immunity over the entire life-span of an organism. Along with other stromal cells, the MSCs form a specialized microenvironment BM tissue called ‘niche’ that tightly controls HSC self-renewal and differentiation. In addition, MSCs are also crucial players in maintaining bone integrity and supply in hormonal nutrients due to their capacity to differentiate into osteoblasts and adipocytes which also contribute to the BM niche network. However, MSC are known to encompass a large heterogenous cell population that remains elusive and poorly defined. In this review, we focus on deciphering the BM-MSC biology through recent advances in single-cell identification of hierarchical subsets with distinct functionalities and transcriptional profiles. We also discuss the contribution of MSCs and their osteo-adipo progeny in modulating the complex direct cell-to-cell or indirect soluble factors-mediated interactions of BM HSC niche during homeostasis, ageing and myeloid malignancies. Lastly, we examine the therapeutic potential of MSC rejuvenation and reprogramming in clinical settings.